2014
DOI: 10.1371/journal.pone.0105783
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Awareness, Knowledge, and Practice among Arab Women in the United Arab Emirates: A Cross-Sectional Survey

Abstract: BackgroundBreast cancer screening can reduce morbidity and mortality and improve the survival rate for this malignancy. Low participation in screening programs has been attributable to many factors including lack of knowledge. The aim of this study was to assess breast cancer screening knowledge, attitudes and practices among women of screening age (≥40 years old) in the city of Al Ain, United Arab Emirates (UAE).MethodsA cross-sectional survey was conducted in 2013 using the Breast Cancer Awareness Measure (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 13 publications
9
91
4
4
Order By: Relevance
“…A majority of existing instruments focus primarily on breast screening behavior as an indicator of breast cancer awareness (Kanaga et al, 2011;Norlaili et al, 2013;Donnelly et al, 2014;Elobaid et al, 2014;Tazhibi and Feizi, 2014). However, several studies (Patel et al, 2003;Liu et al, 2014a;Miyawaki et al, 2014) have advocated the inclusion of health self efficacy and general health awareness as important components of breast cancer awareness.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of existing instruments focus primarily on breast screening behavior as an indicator of breast cancer awareness (Kanaga et al, 2011;Norlaili et al, 2013;Donnelly et al, 2014;Elobaid et al, 2014;Tazhibi and Feizi, 2014). However, several studies (Patel et al, 2003;Liu et al, 2014a;Miyawaki et al, 2014) have advocated the inclusion of health self efficacy and general health awareness as important components of breast cancer awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half (44.8%) of women who never had a clinical breast exam and 44.1 percent of women who never had a mammography expressed a lack of knowledge about the existence of these screening techniques. Nearly one third of the participants interpreted the presence of a breast lump incorrectly and, moreover, expressed fewer worries about the nature of the lump than would normally be expected [19]. [20] have found that poor knowledge and practice of breast screening are likely to lead to late stage presentation of breast cancer disease.…”
Section: Results Andmentioning
confidence: 98%
“…An Arabic and English versions questionnaires were developed and used in the present study which was adapted from a similar studies that were conducted in Al Ain City [8], RAK city [10] and Saudi Arabia [9] and modified to meet our objectives. The self-administered questionnaire contained a total of 102 questions and was divided into four parts that addressed the participants' sociodemographic characteristics (17 questions) and breast cancer screening knowledge (28 questions), attitudes (5 question), and practices (7 questions).…”
Section: Study Instrument and Ethical Approvalmentioning
confidence: 99%
“…It mostly affects Arab women at younger ages compared to women in western countries (WHO). A recent study in 2014 showed that breast cancer was the second leading cause of death among women in Abu Dhabi, comprising 20.3% of the five most common cancers in 2014 [2,3,6]. The impact of breast cancer can be reduced through various practices including breast self-examination (BSE), clinical breast examination (CBE), or obtaining a mammogram.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation